Preferences for Edible and Electronic Leisure Items: A Systematic Replication. (September 2022) - Scheithauer, Mindy; Martin, Clarissa; Bottini, Summer
Early studies evaluating the relative preference for leisure compared with edible items suggested that, for most participants (>80%), edible items are more preferred than leisure items. Recent studies suggest more variability in the percentage of participants with this preference. The rationale for this variability could be sampling, setting, availability of items outside of the study, or the items included. As a systematic replication, we conducted preference assessments of leisure, edible, and leisure/edible items combined of 13 children with developmental disabilities. As an inclusion criterion, all participants had an electronic item as the top-preferred leisure item. An edible item ranked first in the combined assessment for 46.2% of participants. This replicates recent findings while accounting for access to edibles outside of the study. These outcomes are important to guide use of preference assessments across reinforcer classes in clinical and school settings.